Thermal Requirements and Population Viability of Chrysodeixis includens (Lepidoptera: Noctuidae) - Benedito, Antone dos Santos [UNESP]; Fernandes, Odair Aparecido [UNESP]; Ferreira, Claudia Pio [UNESP] (Entomological Soc Brasil, 2021)
Development, mortality, fecundity, and longevity of soybean looper Chrysodeixis includens (Walker) (Lepidoptera: Noctuidae, Plusiinae) were examined at six constant temperatures (18, 22, 25, 28, 32, and 36(circle)C) under laboratory conditions. This set range comprises temperatures observed at soybean- and cotton-producing regions during the growing season. Complete development from egg to adult was observed from 18 to 32(circle)C. Linear and nonlinear models were fitted to the data to estimate thermal constants and bioclimatic thresholds. Although the development of immature stages of C. includens can be expected across broader temperature ranges, this species is meant to complete the whole cycle and recover from low densities between 19.7 and 30.0(circle)C. The best fitness is achieved at 25.4(circle)C. The results can be used to parameterize phenological or mathematical models to forecast the occurrence of different stages of C. includens in the field and help optimize the efforts to control this insect-pest.
Keywords: Thermal biology; life-history traits; intrinsic growth rate; pest control